1997
DOI: 10.1080/027249897392017
|View full text |Cite
|
Sign up to set email alerts
|

Age of Acquisition Norms for a Large Set of Object Names and Their Relation to Adult Estimates and Other Variables

Abstract: Studies of lexical processing have relied heavily on adult ratings of word learning age or age of acquisition, which have been shown to be strongly predictive of processing speed. This study reports a set of objective norms derived in a large-scale study of British children's naming of 297 pictured objects (including 232 from the Snodgrass & Vanderwart, 1980, set). In addition, data were obtained on measures of rated age of acquisition, rated frequency, imageability, object familiarity, picture-name agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
522
4
10

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(568 citation statements)
references
References 26 publications
30
522
4
10
Order By: Relevance
“…For the picture naming task, we selected 16 objects with early-acquired names and 16 with late-acquired names using the picture gallery provided by Snodgrass and Vanderwart (1980) and by Morrison, Chappell, and Ellis (1997). Four homogeneous and four heterogeneous sets each were created of the early-and the late-acquired sets (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…For the picture naming task, we selected 16 objects with early-acquired names and 16 with late-acquired names using the picture gallery provided by Snodgrass and Vanderwart (1980) and by Morrison, Chappell, and Ellis (1997). Four homogeneous and four heterogeneous sets each were created of the early-and the late-acquired sets (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 18 objects had short, monosyllabic names in English, Dutch, and German, while 9 objects had long, three-or four-syllable names in all three languages. Ratings were from the English norms by Morrison, Chappell, and Ellis (1997). Only for bikini were no ratings available, but the item was included given the constraints on appropriate items/words in all three languages.…”
Section: Word Setsmentioning
confidence: 99%
“…Gilhooly and Logie (1980) obtained AoA ratings by requiring participants to estimate at what age they first learned each word, using a 7-point scale (where a rating of I was to given to words acquired between the ages of 0 and 2 years, and a rating of 7 was given to words acquired at age 13 and older). Several studies have shown that these ratings correlate impressively highly with objective measures ofthe age at which words are actually learned, thus validating their use (e.g., Carroll & White, 1973;Lyons, Teer, & Rubenstein, 1978;Morrison, Chappell, & Ellis, 1997). High-frequency words were chosen as having a frequency count (from Kucera & Francis, 1967) ofat least 50 occurrences per million, and low-frequency words had a frequency count offewer than 5 per million.…”
Section: Experiment! Methodsmentioning
confidence: 99%